Tourism-Based English Tourism Teaching Materials to Improve Students’ Literacy and Tourist Visits - Istina Atul Makrifah; Ahmad Saifudin (Journal of Education Reseach and Evaluation, 2026)
The limited availability of contextualized English for Tourism teaching materials grounded in local tourism potential has resulted in learning experiences that are insufficiently aligned with students’ academic and professional needs, particularly in regions with significant tourism resources. Existing instructional materials remain largely generic and have not optimally integrated local tourism contexts, cultural values, or curriculum learning outcomes. This study aimed to develop locally based English for Tourism teaching materials and to examine their validity, practicality, and effectiveness in supporting the learning process. This research employed a Research and Development (R&D) design by adapting the ADDIE model. The participants were a lecturer and sixth-semester students of the English Education Study Program. Data were collected through questionnaires, semi-structured interviews, classroom observation sheets, document analysis forms, and expert validation sheets. The data were analyzed using both qualitative and quantitative descriptive techniques. The findings indicate that the developed teaching materials achieved a validity score of 4.08 from the content expert and 4.09 from the media expert, both categorized as valid. The materials were considered practical based on limited trial results, with an average student response score of 85. Furthermore, they were effective in enhancing students’ comprehension, tourism literacy, and communicative competence. The implications of this study suggest that locally based tourism materials can serve as a model for developing English for Specific Purposes (ESP) instruction, contribute to curriculum development in higher education, and strengthen the role of educational institutions in promoting sustainable regional tourism development.